2016
DOI: 10.18632/oncotarget.12131
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of the lymph node ratio in node positive colorectal cancer: a meta-analysis

Abstract: The lymph node ratio (LNR) (i.e. the number of metastatic lymph nodes divided by the number of totally resected lymph nodes) has recently emerged as an important prognostic factor in colorectal cancer (CRC). However, the tumor node metastasis (TNM) staging system for colorectal cancer does not consider it as a prognostic parameter. Therefore, we conducted a meta-analysis to evaluate the prognostic role of the LNR in node positive CRC. A systematic search was performed in PubMed, Embase and the Cochrane Library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
28
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 44 publications
4
28
0
4
Order By: Relevance
“…In this study, high LNR was significantly associated with low DFS (HR, 2.75; 95% CI, 2.14-3.53; P < 0.001) and OS (HR, 1.91; 95% CI, 1.71-2.14; P < 0.001). In addition, LNR remained a significant prognostic factor regardless of the number of harvested LNs; ≥12 and <12 of harvested LNs (HR, 1.97; 95% CI, 1.71-2.26; P < 0.001 and HR, 1.74; 95% CI, 1.40-2.17; P < 0.001, respectively) [33]. A standard reference value of LNR is required for universal use of LNR for predicting prognosis; however, there is no consensus on what this value should be.…”
Section: Lymph Node Ratiomentioning
confidence: 94%
See 1 more Smart Citation
“…In this study, high LNR was significantly associated with low DFS (HR, 2.75; 95% CI, 2.14-3.53; P < 0.001) and OS (HR, 1.91; 95% CI, 1.71-2.14; P < 0.001). In addition, LNR remained a significant prognostic factor regardless of the number of harvested LNs; ≥12 and <12 of harvested LNs (HR, 1.97; 95% CI, 1.71-2.26; P < 0.001 and HR, 1.74; 95% CI, 1.40-2.17; P < 0.001, respectively) [33]. A standard reference value of LNR is required for universal use of LNR for predicting prognosis; however, there is no consensus on what this value should be.…”
Section: Lymph Node Ratiomentioning
confidence: 94%
“…Some studies reported that LNR only had a significant influence on survival in patients with adequate number of examined lymph nodes (≥10-12) [30,31]; however, a few studies have reported that N staging was superior to LNR in predicting patient survival with a high number of examined lymph nodes [32]. Antithetically, some studies have reported that LNR was an independent prognostic factor for survival, regardless of the total number of examined lymph nodes [33][34][35][36][37][38]. Recent meta-analysis of 33 studies that included a total of 75,839 patients with node-positive colorectal cancer supported these findings.…”
Section: Lymph Node Ratiomentioning
confidence: 99%
“…In contrast to the number of positive lymph nodes alone, especially in stage III colon cancer, the LNR has been shown to reflect outcome. 10 The aim of this study was to compare the location of the colorectal cancer, stage and lymphnode ratio in young (≤40 years) and older patients.…”
mentioning
confidence: 99%
“…It was similar to other studies where the retrieved nodes ranges from 10 to 26.8 nodes, which signifies the adequacy of nodal dissection in our study. 10,18 The cut off LNR has been reported to be 0.12 to 0.35. 10 In our series, the mean LNR was 0.31 in the younger patients where as in those above 40 years, it was 0.13 and the difference was statistically significant.…”
mentioning
confidence: 99%
See 1 more Smart Citation